Math, asked by nashathfazza, 1 year ago

Pls give me the answer of 5th i ii iii iv
With steps
I will wark u as brainliest

Attachments:

Answers

Answered by Hiteshbehera74
0

(i)

 \frac{8}{ - 5}  + ( \frac{4}{ - 3} )  + \frac{1}{3}  \\  =   - \frac{ 8}{5}  -  \frac{4}{3}  +  \frac{1}{3}  \\  =  -  \frac{8}{5}   +  \frac{1 - 4}{3}  =  -  \frac{8}{5}  -  \frac{3}{3} =  -  \frac{8}{5}  - 1  \\  =  \frac{ - 8 - 5}{5}  =  -  \frac{13}{5}

Answered by Anonymous
0

e7ur86rffxufutfifui9

Similar questions